Pengimbuhan Kunyit dan Seng Oksida dalam Pakan Meningkatkan Kemampuan Ayam Pedaging dalam Mengeliminasi Tantangan Infeksi Escherichia coli (SUPPLEMENTATION CUCURMIN AND ZINC OXIDE INCREASE THE ABILITY OF BROILER CHICKENS IN ELIMINATING ESCHERICHIA COLI CH - Widhyari, Sus Derthi; Wientarsih, Ietje (Jurnal Veteriner, 2014)
This study aims to determine the effect of the feed additive (zinc and herbs) in leucocyte profiles,performance, and observe the ability of broiler on E. coli challenge. A total of 160 chickens were dividedinto four groups: Group K-control negativewere given basal diet; Group two were given fed basal, turmeric1.5% + ZnO 180 ppm; Group two were given fed basal, garlic powder 2.5% + Zn0 180 ppm; and group K+ weregiven basal diet and treatment with antibiotics. At the age of three weeks all groups were challenged orallyby inoculation with E.coli at dose of 108CFU/mL. Observed parameters include performance (weight gain,consumption) and total leukocytes. Weight gain, consumption were observed at one to five weeks of age,whereas blood samplings for the examination of leukocytes were performed at week three (pre infection),week four and five (one week and two weeks after infection with E.coli). The results showed that thechicken body weight from age one to three weeks was increased sharply. One week after infection weightloss seemed to be decreased. The largest decrease was observed in the group given the combination ofgarlic-Zn, while providing a combination of curcumin-Zn shows that the weight tends to increase. Rationconsumption showed the same pattern as body weight. The highest consumption at the end of the studywas found in the group given the combination of curcumin - Zn, the lowest was in the garlic-Zn. Highleukocyte cells level at one week post infection, showing an animal in a state of infection and the leucocytedecreasing again at two weeks post infection. The conditions indicate the ability of chickens in eliminatinginfectious agents. These results explain the combination of curcumin-Zn showed the best results comparedwith other treatments. Providing supplementation of curcumin - Zn on chicken improved the ability toeliminate E.coli, leukocyte cell profile, and performance.
Keywords: broiler, E.coli, zinc, garlic, turmeric